98.5k views
2 votes
If
h(x) = (f°
g)(x) and
h(x) \sqrt[3]{x+3}, find
g(x) if
f(x) \sqrt[3]{x+2}

User Giladbi
by
5.0k points

1 Answer

3 votes

Answer:

g(x) = x + 1

Explanation:

h(x)=(f o g)(x)

h(x)=f(g(x)) (Equation 1)


h(x)=\sqrt[3]{x+3}


f(x)=\sqrt[3]{x+2}


f(g(x))=\sqrt[3]{g(x)+2}

Replacing in the Equation 1:


\sqrt[3]{x+3}=\sqrt[3]{g(x)+2}

Solving for g(x): Raising both sides to the power 3:


(\sqrt[3]{x+3})^(3)=(\sqrt[3]{g(x)+2})^(3)

x+3=g(x)+2

Subtracting 2 from both sides of the equation:

x+3-2=g(x)+2-2

x+1=g(x)

g(x)=x+1

User Niko Efimov
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.